"Decompartmentalization": The key technique for interpreting regional human rights treaties. (12th May 2018) - Burgorgue-Larsen, Laurence
Abstract: Judicial and quasi-judicial bodies of the African, Inter-American, and European human rights systems have all developed interpretation techniques which, although based on customary norms codified in the Vienna Convention on the Law of Treaties, regularly distance themselves from such norms. Regional courts and commissions consistently recall how particular human rights treaties are: entirely human-oriented—his/her interest and his/her rights—state sovereignty is not their main raison d'être. On the contrary, they were drafted so that the raison d'etat did not prevail over human rights. We have thus entered an era of "decompartmentalization, " a process allowing the use of external sources of various kinds (national and international, soft and hard law, textual and jurisprudential) to interpret the rights enshrined in the African, Inter-American, and European human rights instruments. Section 1 presents the legal bases of this process. Section 2 focuses on analyzing special features of the practice. Despite maximum decompartmentalization in the three regional systems, two types of differences can be observed (i.e., the particular relationship between regional and domestic courts and the close and complex links between processes of interpretation and application of the law). Finally, Section 3 evaluates the normative and institutional consequences of the decompartmentalized interpretation.